Multilateral diplomacy and the NPT : an insider's account - Dhanapala, Jayantha (UNIDIR, 2005)
Concerns the Nuclear Non-Proliferation Treaty Review and Extension Conference (NPTREC) of 1995.
"Foreword by United Nations Secretary-General Kofi A. Annan"--Cover
"SIPRI"--Cover
"UNIDIR/2005/3"--Title page verso
"United Nations publication. Sales no. GV. E.05.0.5"--Title page verso
Keywords: NPT Review and Extension Conference -- (1995 : -- New York, N.Y.); Traité sur la non-prolifération des armes nucléaires -- (1968 juin 12); NPT Review and Extension Conference; Review Conference of the Parties to the Treaty on the Non-Proliferation of Nuclear Weapons -- (5th : -- 1995 : -- New York, N.Y.); Review Conference of the Parties to the Treaty on the Non-Proliferation of Nuclear Weapons -- (5th : -- 1995 : -- New York, N.Y.) -- Resolutions and decisions.; Review Conference of the Parties to the Treaty on the Non-Proliferation of Nuclear Weapons -- (5th : -- 1995 : -- New York, N.Y.) -- Participants.; Treaty on the Non-Proliferation of Nuclear Weapons (1968); Nuclear nonproliferation -- Congresses.; Diplomacy.; Nuclear disarmament -- Congresses.; Non-prolifération nucléaire -- Congrès.; Désarmement nucléaire -- Congrès.; Diplomatie.; diplomacy.; LAW -- International.; Nuclear disarmament; Diplomacy; Nuclear nonproliferation; Non-proliferatie.; Diplomatieke betrekkingen.; Verdragenrecht.; Diplomacia.; Não-proliferação nuclear.; Tratados internacionais.; Organização intergovernamental.; Política nuclear internacional.; No proliferación nuclear -- Congresos.; DIPLOMACIA.; Tratados internacional.; NUCLEAR NON-PROLIFERATION.; DISARMAMENT AGREEMENTS.; TREATY REVIEW.; CONFERENCES.; TREATIES (TEXT); Conference papers and proceedings